2006 Annual Report on Operations Evaluation - Singh, Janardan Prasad (Independent Evaluation Group Studies, 2006)
The AROE series continues to strengthen its focus on results, monitoring, and evaluation. The latest 2006 edition updates the implications of managing for results in World Bank operations, assesses if monitoring and evaluation practices provide staff with information that helps them manage for results, and looks at IEG's own effectiveness. Its recommendations address ways to make monitoring and evaluation more effective and influential tools